A Review of Cobalt-Based Metal Hydroxide Electrode for Applications in Supercapacitors - Sajid Naeem; Arun V. Patil; Arif V. Shaikh; U. P. Shinde; Dilawar Husain; Md Tanwir Alam; Manish Sharma; Kirti Tewari; Shameem Ahmad; Aqueel Ahmed Shah; Syed Abbas Ali; Akbar Ahmad (Advances in Materials Science and Engineering)
Supercapacitors are the cutting-edge, high performing, and emerging energy storage devices in the future of energy storage technology. It delivers high energy and produces higher specific capacitances. This research study provides insights into supercapacitor materials and their potential applications by examining different battery technologies compared with supercapacitors’ advantages and disadvantages. Transition metal hydroxides (cobalt hydroxides) have been studied to develop electrodes for supercapacitors and their use in various fields of energy and conversion devices. Cobalt-based metal oxides and hydroxides provide high-capacitance electrodes for supercapacitors. Metal hydroxides combine high electrical conductivity and excellent stability over time. The metal oxides used to prepare the electrodes for supercapacitors are cobalt-based metal oxides and hydroxides. It is stronger than most of the other oxides and has tremendous electrical conductivity. Cobalt hydroxides are also used in supercapacitors instead of other metal hydroxides, such as aluminum hydroxide, copper hydroxide, and nickel hydroxide. This study gives a complete overview of the preparation, synthesis, analysis, and characterization of cobalt hydroxide thin film electrodes by using the electrochemical deposition technique, parameters measurements, important characteristics, material properties, various applications, and future enhancement in supercapacitors.